Micro-climatic observations in the primeval forest in Kasuga, Nara: (2) On the comparison between inside and outside of the forest - NAGATA, S. (Journal of Agricultural Meteorology, 1952)
In the 1st report, the relations between the distributions of plants in this Forest and their micro-climatic environments were related. In this report, the comparisons between inside and outside of this Forest are taken up. i.e. Comparisons between the Forest and Nara city on temperature, humidity, precipitation, and temperature variations (Fig 1-3, Table 1-3), and the Forest and Wakakusa-Yama in summer, winter; they seemingly represent good examples of “forest-climate”.